A diagnostic character revisited: is there a fifth toe in the forefoot of Dasypus novemcinctus (Xenarthra: Dasypodidae)? - Costa, Fabiana R.; Vizcaíno, Sergio F. (Zootaxa, 2010)
Armadillos (Xenarthra: Dasypodidae) are among the most conspicuous and peculiar groups of mammals, and are characterized by an armor of osteoderms covered by keratinized scutes. They are widespread in South America, with one species (Dasypus novemcinctus Linnaeus) also reaching southern North America (Wetzel 1985, Aguiar & Fonseca 2008; Gardner 2008). Following the latest revision of the subfamily Dasypodinae (Wetzel & Mondolfi 1979), the single genus Dasypus is partitioned into three subgenera: Dasypus, Cryptophractus and Hyperoambon. Cryptophractus comprises the single species D. pilosus Fitzinger, and Hyperoambon was proposed for D. kappleri Krauss (Gardner 2008). Dasypus(Dasypus) contains five species (Wetzel & Mondolfi 1979; Vizcaíno 1995): D septemcinctus Linnaeus, D. hybridusDesmarest, D. novemcinctus, D. sabanicola Mondolfi and D. yepesi Vizcaíno. Only D. (H.) kappleri is reported to retain five toes in the forefoot (Wetzel & Mondolfi 1979), while D. (Dasypus) and D. (C.) pilosus are described as having only four toes on the forefoot (Hamlett 1939; Wetzel & Mondolfi 1979), the middle pair being the largest. D. (C.) pilosus is an enigmatic species because little is known about most aspects of its biology and morphology (see Vizcaíno & Loughry 2008). Much more has been published on the species of D. (Dasypus), particularly D. novemcinctus. Despite the substantial literature on this species (see Vizcaíno & Loughry 2008 for an extensive compilation), little is known about several aspects of the descriptive (e.g. Taylor 1976; Windle & Parsons 1899) and functional (e.g. Vizcaíno & Milne 2002) morphology of its limbs. Detailed studies on its fore and hindfeet morphology are not available.